2020
DOI: 10.1155/2020/6969053
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of rhBNP on Postresuscitation Myocardial Dysfunction in a Rat Cardiac Arrest Model

Abstract: Purpose. We investigated the protective effects and the underlying mechanisms through which recombinant human brain natriuretic peptide (rhBNP) acts on postresuscitation myocardial dysfunction (PRMD) in the cardiac arrest (CA) model. Methods. Ventricular fibrillation was induced and untreated for 6 min. And the time of cardiopulmonary resuscitation was 8 min, after which defibrillation was attempted in this rat model. 24 Sprague Dawley rats (450–550g) were randomized into cardiopulmonary resuscitation (CPR) + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…C23 and TLR4 have a strong a nity, thus inhibiting CIRP binding to TLR4/MD2 complex [13]. Toll-like receptors are widely expressed in brain tissues, myocardial tissues, and serum in CA/CPR model [33][34][35][36]. Both the PAMPs and DAMPs can activate TLR4 receptors on the surface of cells.…”
Section: Discussionmentioning
confidence: 99%
“…C23 and TLR4 have a strong a nity, thus inhibiting CIRP binding to TLR4/MD2 complex [13]. Toll-like receptors are widely expressed in brain tissues, myocardial tissues, and serum in CA/CPR model [33][34][35][36]. Both the PAMPs and DAMPs can activate TLR4 receptors on the surface of cells.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are compelling in that they provide evidence that attenuation of mitochondrial injury and reactive oxygen species generation during cardiac arrest can lead to meaningful outcomes, and encourages further work on this aspect using larger animal models and mechanistic studies [11]. In another preclinical rat model, recombinant human brain natriuretic peptide (rhBNP) was administered following return of spontaneous circulation (ROSC ) in order to regulate expression of nuclear transcription factor kappa B as a way to attenuate injurious cellular injury pathway [12]. The authors found that animals receiving the rhBNP had improved survival rates at 24 hours post-ROSC, reduced myocardial tissue injury and reduced circulating levels of interleukin 6 and tumor necrosis factor alpha over controls, suggesting a protective effect [12].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…In another preclinical rat model, recombinant human brain natriuretic peptide (rhBNP) was administered following return of spontaneous circulation (ROSC ) in order to regulate expression of nuclear transcription factor kappa B as a way to attenuate injurious cellular injury pathway [12]. The authors found that animals receiving the rhBNP had improved survival rates at 24 hours post-ROSC, reduced myocardial tissue injury and reduced circulating levels of interleukin 6 and tumor necrosis factor alpha over controls, suggesting a protective effect [12].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…Postresuscitation myocardiac dysfunction, an important component of the postcardiac arrest syndrome, is caused by ischemia/reperfusion (I/R) injury and includes primary manifestations such as arrhythmias, myocyte apoptosis, and contractile dysfunction [ 3 ]. Furthermore, post-resuscitation myocardial dysfunction is considered the leading cause of death within 72 h after successful CPR [ 4 ]. Therefore, studies of new medications that aim to improve post-resuscitation myocardial dysfunction are of great urgency and importance.…”
Section: Introductionmentioning
confidence: 99%